Influence of concentration and the heat transfer for a ferromagnetic fluid in a porous medium - Majeed, Firdews G.; Hummady, Liqaa Z. (Iraqi Journal of Science, 2025)
This article studies and examine the concentration and heat transfer under long wavelength conditions in an asymmetric channel with a porous medium while an applying a magnetic field and rotation to the peristaltic flow Powell-Eyring. Considering low Reynolds numbers, all nonlinear partial differential equations are extracted using the perturbation method and MATHEMATICA, (19) program. The fluid is subject to a magnetic field and changes in concentration. As it flows within a porous medium, we have used a set of parameters and compared them in terms of (velocity, pressure). Examples of these parameters are Hartmann number (Ha), Darcy number (Da), rotation (Ω), etc. We notice that some parameters affect the increase in velocity and others affect the decrease in velocity, and the same applies to pressure. We use graphs to express the speed and pressure gradient and their effect on the parameters affecting the equations of motion. Using a set of numbers to produce numerical results, the impact of various parameters is explored below and illustrated graphically.